2017
DOI: 10.1177/1753944717704590
|View full text |Cite|
|
Sign up to set email alerts
|

DUSP-1 gene expression is not regulated by promoter methylation in diabetes-associated cardiac hypertrophy

Abstract: Methylation-mediated silencing of the DUSP-1 promoter does not appear to be associated with reduced expression, indicating the involvement of other factors in specific suppression of DUSP-1 in diabetes-associated cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…High DUSP1 expression can be found in several tissues, including the heart, lungs, and liver [21]. In the heart, DUSP1 regulates cardiac metabolism, and the inhibition of DUSP1 (or MKP1) was reported to induce cardiac hypertrophy in a transgenic mouse model [22]. In addition, a study by Weng et al reported that the expression of DUSP1 was low in the myocardium of a diabetic rat; this suggests that the abnormal expression of DUSP1 might involve the pathophysiology of diabetic cardiomyopathy [23].…”
Section: Introductionmentioning
confidence: 99%
“…High DUSP1 expression can be found in several tissues, including the heart, lungs, and liver [21]. In the heart, DUSP1 regulates cardiac metabolism, and the inhibition of DUSP1 (or MKP1) was reported to induce cardiac hypertrophy in a transgenic mouse model [22]. In addition, a study by Weng et al reported that the expression of DUSP1 was low in the myocardium of a diabetic rat; this suggests that the abnormal expression of DUSP1 might involve the pathophysiology of diabetic cardiomyopathy [23].…”
Section: Introductionmentioning
confidence: 99%
“…DCM is characterized by structural and functional abnormalities in the myocardium such as cardiac fibrosis, ventricular hypertrophy and heart failure . Several mechanisms have been implicated to be associated with the pathogenesis of DCM, including myocardial insulin resistance, cardiac inflammation, oxidative stress, interstitial fibrosis, cardiac cell death and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…18 It still remains a great challenge to explain the underlying mechanism involved in myocardial remodeling. It is well-known that the dual speci city phosphatases (DUSPs) family involved in the development of myocardial remodeling [19][20][21]. [19][20][21] However, the role of DUSPs varies under different stimulation and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%